Being Poor, Feeling Poorer : Inequality, Poverty and Poverty Perceptions in the Western Balkans - Koczan, Zsoka (IMF Working Papers; Working Paper, 2016)
Emerging Europe has undergone a major economic transformation over the past 25 years. Most countries experienced initial drops in output during transition, followed by recovery in the second half of the 1990s. The path of transition in the Western Balkans has however been particularly uneven. The effects of transition also seem to have been more traumatic and persistent in the Western Balkans, and nostalgia for the past appears to be more prevalent here than in other former communist regions. Such dissatisfaction has important implications for the political economy of further reforms. This paper aims to inform policy by complementing the analysis of standard macro-level measures of inequality and poverty with a household-level analysis of subjective perceptions of poverty. We find that many more people appear to feel poor than are classified as such using purely income-based measures. Uncertainty, in particular related to expectations of future income and vulnerability to shocks, appears to be a key driver behind this discrepancy.